The COVID-19 and Its Effect on Small Businesses in Nigeria: A Rational Choice Theory and an Empirical Approach - Ademola Samuel Sajuyigbe; Anthony Abiodun Eniola; James Nwoye Obi; Fred Ojochide Peter (Journal of Accounting and Strategic Finance, 2021)
The misery and difficulties of the novel deadly infection (COVID-19) are of great concern to analysts, researchers, policymakers, and government agencies over the globe. This investigation examines the effect of the deadly infection (COVID-19) on small businesses in Nigeria, with particular reference to Lagos State. A purposive examining procedure was utilized to choose each of the 321 small businesses owner of Nigeria (ASBON) enlisted in the Lagos Business Directory. Close-ended questionnaires were used to gather data from the members. The data analysis was performed with percentage, mean, chi-square, and component factor analysis. The outcome uncovers that the deadly infection (COVID-19) has injured all the SMEs surveyed. It was discovered that most small businesses are doomed as a result of the negative impact of COVID-19. The assessment using rational choice theory derives that credit accessibility, tax waiver for sectors, the introduction of emergency advances, and flexibility of repayments of existing loans by financial institutions are solid palliative measures that can cushion the effect of the deadly infection (COVID-19).